Cytoprotective Potential of Spondias mombin fractions on Sodium Arsenite-Induced Haematological, Biochemical and Genotoxic Perturbations in Rats (African Journal of Biomedical Research, 2019)
Heavy metals are leading causes of environmental contamination and arsenic (As) is currently one of the most important metal contaminants particularly in the developing countries such as Nigeria. The effects of chromatographic fractions of Spondias mombin L. (SM) leaves on sodium arsenite-induced toxicities in male Wistar rats were evaluated. Thirty-five male rats allotted equally into seven groups (A – G): Groups A and B were treated with 0.1 mL 1% dimethylsulphoxide (DMSO) and distilled water respectively, Group C: sodium arsenite (SA) 2.5 mg/kg, Group D: 100 mg/kg ethyl acetate fraction of SM, Group E: 100 mg/kg ethyl acetate fraction of SM and 2.5 mg/kg SA, Group F: 100 mg/kg methanol fraction of SM and SA, Group G: 100 mg/kg methanol fraction. SM was administered orally for 14 days, while SA was administered as a single oral dose on the 14th day of treatment with SM. Blood was taken 24 hours after SA administration and the animals were sacrificed. Phytochemical, haematological, biochemical, histopathological analyses and micronucleated polychromatic erythrocytes (MnPCEs) induction in the bone marrow cells were evaluated at the termination of the experiment. Phytochemical screening revealed alkaloids, tannins, phenols and flavonoids in all the fractions. Ethyl acetate and methanol fractions contained cardiac glycosides and carbohydrates whereas only hexane and ethyl acetate fractions contained steroids. Results showed normocytic hypochromic anaemia, genotoxicity, kidney and perilobular hepatic damage in the group that received SA alone, which were significantly (p